PERFORMANCE MANAGEMENT IN CIVIL ENGINEERING: A SYSTEMATIC LITERATURE REVIEW (Advances in Civil and Architectural Engineering, 2022)
The construction industry is generally one of the fundamental industries of a country, weighing between 5 to 10% of the gross domestic product. Rapid changes in the construction environment require a great deal of effort for a company or project manager to maintain the project successfully. To do so, applying performance management is of crucial importance. Therefore, a systematic literature review was conducted to detect new trends and highlight the evolvement of this research topic. The conducted bibliometric analysis resulted in 1240 documents published in Scopus and Web of Science databases in the period from 2000–2021. The bibliometric indicators, network citations, and multivariate statistical analysis were obtained using JabRef, OpenRefine, Excel, and VOSviewer tools. The co-occurrence analysis showed three keywords clusters as current research hotspots that may be considered as potential research topics in the future: (1) value management in the construction industry, (2) organisation innovation and knowledge management in a particular company, and (3) project management tools and techniques for a particular construction project.